Clinical practice guidelines for laboratory diagnosis of epidermolysis bullosa. (9th August 2019) - Has, C.; Liu, L.; Bolling, M.C.; Charlesworth, A.V.; El Hachem, M.; Escámez, M.J.; Fuentes, I.; Büchel, S.; Hiremagalore, R.; Pohla‐Gubo, G.; van den Akker, P.C.; Wertheim‐Tysarowska, K.; et al.
Abstract : Linked Comment:  Uitto. Br J Dermatol 2020; 182 :526–527 . Plain language summary available online